Histological and behavioral characterization of a murine model of Parkinson's disease using systemic inoculation with Western equine encephalitis virus - Thomas, Samantha Monica, author; Kendall, Lon V., advisor; Tjalkens, Ronald, committee member; Kading, Rebekah, committee member (Colorado State University. Libraries, 2025)
Parkinson's disease (PD) is the second-most common neurodegenerative disease after Alzheimer's disease, constituting over 10 million ongoing cases in humans worldwide. Disability associated with deprecations in motor function in PD is substantial, highlighting the need for better animal models to study interventions. Although the causes of PD are largely unknown, infection with mosquito-borne alphaviruses, such as Western equine encephalitis virus (WEEV), induces symptoms in humans that closely resemble those of PD. This suggests that viral inoculation may be an appropriate model to study the disease in vivo. Intranasal inoculation of mice with WEEV induced dopaminergic neuronal loss in the striatum (ST) and substantia nigra pars compacta (SNpc), a key pathologic feature of PD in humans. However, significant mortality in animals results from this potent, direct impact on brain tissues. This requires adjunctive immunotherapy to improve survivability. Footpad inoculation, however, may prove to be a better model due to an indirect, gradual hematologic spread to the brain. Additionally, footpad inoculation may more closely replicate central nervous system (CNS) pathology, as it mimics the natural route of infection with this mosquito-borne virus. We hypothesize that systemic WEEV infection will induce behavioral and histopathologic changes resembling PD without requiring adjunctive immunotherapy. First, a dose escalation study was performed to evaluate the tolerability of mice to increasing doses (0.5 x 104, 1 x 104, 2 x 104, 0.5 x 105, 1 x 105, and 2 x 105 PFU) of WEEV inoculated subcutaneously into the hind footpads. Clinical observations, body weights, bioluminescent imaging, and behavioral testing, including a pole test and a grid hang test, were performed at various time points prior to brain tissue collection to evaluate the loss of dopaminergic neurons in the ST and SNpc. It was determined that while mice displayed difficulty recovering from anesthesia associated with imaging, the highest viral dose displayed the most consistent pathologic findings. However, behavioral testing was inconsistent as it was determined that the hang test was not suitable, and the pole test needed modifications to improve grip. Finally, C57BL/6 mice were inoculated with 2 x 105 PFU of systemic WEEV to characterize the behavioral and histopathologic traits of the model fully. Observations, weights, and behavioral testing were performed at various time points before brain tissue collection at 14- and 42-days post-infection (dpi) for histopathology and plaque assays. No mortality was seen in this study, indicating that the mortality seen in the dose escalation study mice was likely related to sensitivity to anesthesia induced by systemic WEEV infection. A grip strength meter replaced the hang test, and the pole test was modified for better traction. Mice displayed significant deficiencies in both grip strength and motor coordination by 42 dpi. Plaque assays indicated increasing viral CNS titers from 14 dpi to 42 dpi. Thus, we identify key characteristics of a PD phenotype in a suitable systemic WEEV model of PD. Future studies can utilize this mouse model to investigate novel therapeutic and neurodegenerative-reducing strategies for viral Parkinsonism. This mouse model will also be used in combination with other PD risk factors, such as manganese, to create a dual-hit model to more completely recapitulate the disease process.